Development of model for prediction of Leachate Pollution Index (LPI) in absence of leachate parameters. (May 2017) - Lothe, Anjali G.; Sinha, Alok
Highlights: Development of model to predict Leachate Pollution Index (LPI) for partial data. Plot of normalized ∑ i = 1 n p i w i vs % error resulted in family of lines. Upper limit and lower limits of % error and LPI predicted by model. Geometric mean of upper and lower limit resulted in ±20% error for ∑ i n w i ⩾ 0.6 . Abstract: Leachate pollution index (LPI) is an environmental index which quantifies the pollution potential of leachate generated in landfill site. Calculation of Leachate pollution index (LPI) is based on concentration of 18 parameters present in leachate. However, in case of non-availability of all 18 parameters evaluation of actual values of LPI becomes difficult. In this study, a model has been developed to predict the actual values of LPI in case of partial availability of parameters. This model generates eleven equations that helps in determination of upper and lower limit of LPI. The geometric mean of these two values results in LPI value. Application of this model to three landfill site results in LPI value with an error of ±20% for ∑ i n w i ⩾ 0.6 .